STRATEGI PEMERINTAH DALAM MENGURANGI ANGKA KEMATIAN IBU (AKI) MELAHIRKAN DI KABUPATEN ENREKANG - Ainun Irada Darungan; Abdul Kadir; Nasrul Haq (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2020)
This study purposed to find out how the institutionalization of government strategy in reducing maternal mortality rate (AKI) and how to operationalize the government strategy in reducing maternal mortality rate (AKI) in Enrekang Regency. This study used descriptive qualitative research . Data collection techniques were observation, interviews with 5 informants and documentation. Data analysis used interactive analysis models and used 3 types of triangulation in data validation. The results of this study showed that the role of public health midwives in reducing maternal mortality was very important, especially in the role of community empowerment, optimizing Integrated Healthcare Center activities, and leadership roles in public health and health cadres were expected to be able to encourage the community to carry out self-help activities in improving health status. The role of community health workers in empowering cadres was very important by increasing the ability of community knowledge and awareness regarding prevention of maternal mortality in Enrekang Regency